2019
DOI: 10.12737/stp-51201905
|View full text |Cite
|
Sign up to set email alerts
|

Statistical relationships between variations of the geomagnetic field, auroral electrojet, and geomagnetically induced currents

Abstract: Using observations from the IMAGE magnetic observatories and the station for recording geomagnetically induced currents (GIC) in the electric transmission line in 2015, we examine relationships between geomagnetic field and GIC variations. The GIC intensity is highly correlated (R>0.7) with the field variability |dB/dt| and closely correlated with variations in the time derivatives of X and Y components. Daily variations in the mean geomagnetic field variability |dB/dt| and GIC intensity have a wide night m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 19 publications
(21 reference statements)
4
4
0
Order By: Relevance
“…A broad distribution of nighttime MPEs appeared at all five stations between 1700 and 0100 MLT, and a narrower distribution appeared at the lower latitude stations between 0200 and 0700 MLT. This is consistent with earlier studies by Viljanen et al (2001), Viljanen andTanskanen (2011), Juusola et al (2015), and most recently by Vorobev et al (2019) that showed both "pre-" and "postmidnight" occurrence peaks. Our study has shown that MPEs occurring within 30 min of a substorm onset dominated in nearly all MLT bins at each station 3.…”
supporting
confidence: 93%
“…A broad distribution of nighttime MPEs appeared at all five stations between 1700 and 0100 MLT, and a narrower distribution appeared at the lower latitude stations between 0200 and 0700 MLT. This is consistent with earlier studies by Viljanen et al (2001), Viljanen andTanskanen (2011), Juusola et al (2015), and most recently by Vorobev et al (2019) that showed both "pre-" and "postmidnight" occurrence peaks. Our study has shown that MPEs occurring within 30 min of a substorm onset dominated in nearly all MLT bins at each station 3.…”
supporting
confidence: 93%
“…A similar propagation has been observed before, but only for major geomagnetic storms (Schillings et al., 2022). In this study we have shown that such an MLT propagation also can occur during non‐stormy times. The existence of a midnight and a morning MLT hotspot is known from before (Engebretson et al., 2021; Juusola et al., 2015; Kataoka & Pulkkinen, 2008; Schillings et al., 2022; Viljanen et al., 2001; Vorobev et al., 2019; Weigel et al., 2002), but in this study we showed that the hotspots also are activated during non‐stormy times and during all solar cycle phases (Figure 4). We have shown that spikes are more common in the declining phase of the solar cycle, and this is the case both for non‐stormy times as well as for other geomagnetic activities (Figure 6–7).…”
Section: Summary and Discussionsupporting
confidence: 50%
“…Like the Disturbed Storm Time index (Dst), SYM‐H is designed to measure disturbances in the symmetric ring current, but it has a higher resolution than the Dst index (1 min instead of 1 hr) (Wanliss & Showalter, 2006). A geomagnetic storm is typically considered intense if Dst < − 100 nT, moderate if −100 nT < Dst < − 50 nT, and small if −50 nT < Dst < − 30 nT (Gonzalez et al., 1994; Vorobev et al., 2019). Moreover, so called Sudden Commencements (SC) correspond to positive Dst and SYM‐H excursions, and they can be caused by, for example, interplanetary shocks (e.g., Lühr et al., 2009).…”
Section: Instrumentation Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viljanen et al (2001), Apatenkov et al (2004), and Viljanen and Tanskanen (2011) showed the existence of morning maxima in the MLT occurrence of large ground dB/dt at auroral zone magnetometers. A large number of major GIC events has also been observed in this morning MLT sector (e.g., Viljanen et al, 2001Viljanen et al, , 2014Vorobev et al, 2019), in the same sector where the omega bands occur (e.g., Partamies et al, 2017). The recent statistics of large dB/dt events (Engebretson et al, 2019) associated with magnetic impulsive events (MIE) showed similar MLT distributions with premidnight and morning MLT maxima.…”
Section: Geophysical Research Lettersmentioning
confidence: 91%